Odra – rzeka ekoparadygmatyczna - Barcz, Anna (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
The author aims at presenting examples of literary descriptions of Odra flooding (especially in the context of the most recent in 1997 and 2010) and the river regions in the perspective of aquacriticism. This approach belongs to a wider concept of ecocriticism which perceives the river as a key part of environment. The question being posed is what kind of influence can be traced in literary texts representing floods and how does literature influence perception of aquatic catastrophes such as floods. Since flood belongs to the catastrophe discourse, it blurs anthropocentric knowledge on rivers and indicates aquacentric modes of recognition. The ecoparadigmatic role of Odra is indicated by Silesian authors (in the collection Wie die Oder rauscht ) and writers biographically connected with the river (Tokarczuk). The environmental function of the river can be better acknowledged through literary fiction that “gives voice to the river”.